Disseminated tuberculosis in a patient with antinuclear antibody-negative systemic lupus erythematosus: a rare association. (29th January 2013) - Kumar, Naveen; Aggarwal, Puneet; Dev, Nishanth; Kumar, Gunjan
Abstract : Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease with diverse manifestations. Tuberculosis is known to induce and exacerbate SLE and it becomes quite difficult to diagnose tuberculosis in this setting, owing to a similar, overlapping presentation of tuberculosis and SLE. We report a case of disseminated tuberculosis in a patient with antinuclear antibody-negative SLE. Treatment was started with antitubercular drugs together with hydroxychloroquine and steroid. After 6 months of follow-up the patient recovered with treatment.